Assessment of Obsessive Thoughts About COVID-19 in 7 Latin American Countries: Structure and Measurement Invariance of the Obsession With COVID-19 Scale (2023)
The present study aimed to evaluate the measurement invariance of the Obsession with COVID-19 Scale (OCS) among seven Latin American countries: Bolivia, Brazil, Cuba, El Salvador, Guatemala, Paraguay, and Uruguay. Although the OCS has been used in several countries and languages, there is a need for approaches that better integrate the cross-cultural equivalence of the scale. A total of 3185 people participated in the study. The results indicated the presence of a unidimensional structure and good reliability indices for the OCS in each country. The alignment method indicated that the OCS is an invariant measure of COVID-19 obsession among the populations of seven Latin American countries. The findings based on IRT analysis indicated that all OCS items had adequate discrimination and difficulty parameters. The findings contribute to the understanding of the internal structure of the scale in different countries at the same time, something that has been pending evaluation.